Village Funding Governance and Administrative Capacity: A Systematic Review on Their Role in Community Empowerment - Muhammad Hafiz; Fitri Eriyanti; Zul Fahmi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to systematically examine the role of village fund governance and administrative capacity in shaping community empowerment outcomes. Grounded in public administration, fiscal decentralization, and participatory governance perspectives, this review synthesizes peer-reviewed articles published between 2021 and 2025 and indexed in Scopus, Web of Science, and nationally accredited Indonesian journals (SINTA). To ensure the relevance and feasibility of the study, a bibliometric analysis was conducted using Harzing’s Publish or Perish and VOSviewer to map publication trends, thematic clusters, and the conceptual evolution of research on village funding, governance, and empowerment. The findings indicate that the effectiveness of village funds is strongly mediated by governance quality particularly transparency, accountability, participation, and effectiveness as well as by multidimensional administrative capacity encompassing financial management, human resources, institutional arrangements, and risk management. Empirical evidence consistently demonstrates that well-governed village funds contribute positively to economic self-reliance, social inclusion, and citizen participation. Nevertheless, limited administrative capacity and weak institutional coordination remain significant challenges to achieving sustainable community empowerment.